Heat-induced unfolding facilitates plant protein digestibility during in vitro static infant digestion. (1st May 2022) - Tang, Jiaying; Wichers, Harry J.; Hettinga, Kasper A.
Highlights: Heating of soy and pea protein was done in the context of infant in vitro digestion. Heating soy and pea protein from 65 to 100 °C led to increased protein unfolding. Protein unfolding was manifested by an increased surface hydrophobicity. Surface hydrophobicity was positively correlated with the degree of hydrolysis. Heat-induced protein unfolding contributed to a higher level of digestion. Abstract: Soy protein is the main protein source for plant-based infant formula, whereas pea protein is considered as a potential alternative plant protein source. This study assessed the structural changes of soy and pea proteins after heating between 65 °C and 100 °C, and its effects on the in vitro digestibility in the context of infant digestion. We found that with increased heating intensity, both soy and pea proteins unfolded, manifested as the increased surface hydrophobicity, thereby potentially improving the accessibility to digestive enzymes. Their final in vitro digestibility increased from ∼ 30% of non-treated samples to ∼ 60% of 100 °C-heated samples for soy protein, and from ∼ 52% to ∼ 65% for pea protein. Surface hydrophobicity was strongly positively correlated to the overall digestibility. Therefore, the heating temperatures that enabled protein unfolding promoted the digestibility of soy and pea proteins under infant digestion conditions.